2012
DOI: 10.1186/2046-4053-1-43
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for randomized clinical trial protocol content: a systematic review

Abstract: BackgroundAll randomized clinical trials (RCTs) require a protocol; however, numerous studies have highlighted protocol deficiencies. Reporting guidelines may improve the content of research reports and, if developed using robust methods, may increase the utility of reports to stakeholders. The objective of this study was to systematically identify and review RCT protocol guidelines, to assess their characteristics and methods of development, and to compare recommendations.MethodsWe conducted a systematic revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 50 publications
0
52
0
3
Order By: Relevance
“…13,14 We recorded voices, characterized, and sorted. In sorting, a researcher marked key phrases that indicated items.…”
Section: Methodsmentioning
confidence: 99%
“…13,14 We recorded voices, characterized, and sorted. In sorting, a researcher marked key phrases that indicated items.…”
Section: Methodsmentioning
confidence: 99%
“…Careful development of a clinical trial protocol is important for researchers, ethics review boards, funders, and journals [14, 15]. Protocol reporting guidelines ensure that the specifics of the planned research trial are reported in a transparent, accurate, standardized manner [14, 16].…”
Section: Introductionmentioning
confidence: 99%
“…Protocol reporting guidelines ensure that the specifics of the planned research trial are reported in a transparent, accurate, standardized manner [14, 16]. For reporting trial protocols, the Standard Protocol Items: Recommendations for Interventional Trials (SPIRIT) guideline [15] provides recommendations for essential elements to address in a clinical trial protocol.…”
Section: Introductionmentioning
confidence: 99%
“…The development of a clinical training protocol based on current training practices is considered an initial and necessary step towards developing evidence-based training models (Tetzlaff, Chan, et al, 2012; Tetzlaff, Moher, et al, 2012). In the current study, we chose to report similarities and differences in expert opinion.…”
Section: Introductionmentioning
confidence: 99%